The Effect of the Problem-Based Learning Model Assisted by Teaching Aids on Student Learning Outcomes in the Growth and Development of Living Things Subject in Grade XI of SMAN 17 Medan in the 2025/2026 Academic Year - Irma Tambunan; Masdiana Sinambela2 (UNIVERSITAS PGRI MADIUN, 2026)
This study aimed to determine the effect of the Problem-Based Learning model with aids for teaching aids on student learning outcomes in the growth and development of living things in grade XI of SMAN 17 Medan. The study population was all 280 grade XI students at SMAN 17 Medan. The sample size was 70 students from two classes: an experimental class taught using the PBL model with aids for teaching aids and a control class taught using the PBL model without aids for teaching aids. The research instrument was a validated multiple-choice learning outcome test. The results showed a significant difference between the learning outcomes of students taught using the PBL model with aids for teaching aids and those taught using the PBL model without aids for teaching aids. The t-test showed a calculated t-value > t-table (8,020 > 1,995) at a significance level of 0.05, indicating that Ho was rejected and Ha was accepted.